Saluti da Clerville: L’immaginazione spaziale in Diabolik - Bandirali, Luca (Mediascapes journal, 2023)
This contribution aims to propose a geocritical reading of Diabolik in accordance with the approaches of literary geography and its application to comics (Dittmer 2014). The world constructed by Angela and Luciana Giussani is examined by considering it a product of spatial imagination (Bulson 2007; Tally Jr 2019) with an urban vocation (Fraser 2019). The map of Diabolik's fictional world is also described, and then two illustrative cases of spatial production are analyzed, consisting of the albums Paura (Fear, 1967) and L’idolo della vendetta (The Idol of Vengeance, 2020), presenting some recurring communicative attitudes.